MENGGUNAKAN DAN MENGINTERPRETASIKAN EXPLORATION FACTOR ANALYSIS: PANDUAN BAGI PENELITI DAN MAHASISWA - Adnan Sauddin (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2014)
How should we draw the relationship between each variable in a study included a number of variables, especially research that is very much. A simple question, but it will have a profound effect on the validity of the research is not done. Factor analysis is a statistical analysis technique that can help conduct research on a set of variables in the grouping factors, where each variable in the variable has a large variance. The use of statistical science as a tool to analyze, especially if the use of statistical science aided by using software such as Minitab, SPSS, SAS. That uses software to calculate statistics, an expression of